2018
DOI: 10.1039/c8ra02926a
|View full text |Cite
|
Sign up to set email alerts
|

Convenient chirality transfer from organics to titania: construction and optical properties

Abstract: Polyethyleneimine (PEI) complexed with chiral d- (or l-) tartaric acid (tart) in water can self-organize into chiral and crystalline PEI/tart assemblies which can prompt titania deposition and impart their chirality to the resulting titania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This is the same observation as in our previously reported case, where sub-10 nm crystals of titania were uniformly located through the continuous silica phase so that the titania nanocrystals could not fuse each other to change their morphology at high temperature. 49 From the elemental mapping in the SEM images, we found that Ti, Si and O were homogeneously dispersed throughout the surface. Furthermore, the Ti content in the hybrid surfaces appears to be 28%–29% without apparent differences between the cases of enantiomeric pureness and enantiomeric excess (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This is the same observation as in our previously reported case, where sub-10 nm crystals of titania were uniformly located through the continuous silica phase so that the titania nanocrystals could not fuse each other to change their morphology at high temperature. 49 From the elemental mapping in the SEM images, we found that Ti, Si and O were homogeneously dispersed throughout the surface. Furthermore, the Ti content in the hybrid surfaces appears to be 28%–29% without apparent differences between the cases of enantiomeric pureness and enantiomeric excess (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Silica and titania are structural analogues when they are produced via hydrolytic polycondensation. 49 They are formed by the similar covalent bond of Si-O and Ti-O, respectively, with a tetraoxycoordinated structure. Although we have succeeded in employing the chiral crystalline complex of PEI/Tart for the construction of chiroptical minerals of silica and titania, as well as their application in developing chiroptical materials, [50][51][52][53][54][55][56][57][58][59] the relationship between the component of the catalytic templates and the chiroptical activity of the silica/titania are still not well understood.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] To begin with, it is not well reaction matrix for synthesis of chiroptical polymers although there are great achievements in both syntheses and property regarding chiral inorganic materials. [36][37][38][39][40] We have established a unique method for the synthesis of nanofiber-based chiral silica via an enantioselective pathway, by which the asymmetrical centers of silanes would be selectively generated in siliceous matrixes. [41][42][43][44][45] We revealed that polyethyleneimine (PEI) with secondary amine units (CH 2 NHCH 2 ) in the main chain could self-assemble into crystalline fibrils which can play as a catalytic template to promote the silicification exclusively on its crystalline surface.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are lots of reports on organic and/or inorganic achiral luminophores with an outstanding luminescent property, chiral host materials for the CPL‐active system mostly come from chiral organics. In the field of chiral materials, although there are great achievements in the development of inorganic chiral materials, its potential to a chiral source for the CPL system has been rarely explored. Herein, we propose a new concept for the architecture of solid‐state CPL‐active materials based on host‐guest systems employing the inorganic chiral silica as a chiral host, which can force diverse achiral luminophores (guests) to become CPL‐active.…”
Section: Introductionmentioning
confidence: 99%